100 questions & answers about peripheral artery disease (PAD) 2026-02-15T21:23:59+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Mohler, Emile R.; Hirsch, Alan T. (Alan Tick) (100 questions & answers, 2010)

(untitled)
"What is Pad? What are the symptoms of PAD? Is there a cure for PAD? When might I need an angioplasty? How do I gain control over my life now that I have PAD?" -- Cover, p.1